Visitors satisfaction towards facilities of the giant panda conservation centre, Zoo Negara Malaysia: an exploratory analysis - Johari, Shazali; Yee, Thoo Poh (Taylor's University, 2016)
Understanding visitor satisfaction level is essential to attracting and retaining visitors. The purpose of this study is to evaluate visitor satisfaction towards the Giant Panda Conservation Centre (GPCC) facility. GPCC is the latest main attraction in Zoo Negara where two giant pandas, which come under the Malaysia-China Giant Panda International Conservation Agreement programme, are located and exhibited for visitors. To date, there has been no significant research done regarding visitor satisfaction on the facilities at GPCC. We used a quantitative method and employed a purposive sampling approach. The level of visitor satisfaction was measured using a four-point Likert scale. A self-administered questionnaire was used to survey a sample of 250 visitors. The data gathered were analysed using descriptive analysis. Results indicate that the visitors were satisfied with the overall facilities provided. However, there were a few facilities which gained lower satisfaction levels from the visitors. Therefore, the GPCC management should continue to maintain the standard of facilities that they are providing and take serious consideration in improving on those that recorded lower satisfaction.